2009
DOI: 10.1007/s10705-009-9324-1
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and phosphate balance on crop production in Japan on national and prefectural scales

Abstract: Trends in nitrogen (N) and phosphate (P) balance for several crops were calculated for the nation and by prefecture for 5-year periods from 1985 to 2005. Prefectural chemical N and P fertilizer applications for paddy rice and upland crops declined but applications for vegetable crops increased during the period like as national trends. Prefectural chemical N and P applications for tea, orchard and forage remained unchanged in line with national trends. Manure N and P applications for each crop did not follow t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…This means that the use of AM fungal inoculum is valuable for farmers. Heavy application of phosphate fertilizer has been carried out on horticultural crops (Mishima et al 2010;Reijneveld et al 2010). Rock phosphate has been used to produce phosphate fertilizers, and availability of rock phosphate may peak in about 2030 (Cordell et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This means that the use of AM fungal inoculum is valuable for farmers. Heavy application of phosphate fertilizer has been carried out on horticultural crops (Mishima et al 2010;Reijneveld et al 2010). Rock phosphate has been used to produce phosphate fertilizers, and availability of rock phosphate may peak in about 2030 (Cordell et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Mishima et al (2010) showed that the P surplus was larger than the N surplus in Japan. As a result, the concentration of available P in agricultural soil has been increasing (Obara and Nakai 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the concentration of available P in agricultural soil has been increasing (Obara and Nakai 2004). Mishima et al (2010) calculated that 20% of the P applied to agricultural land was derived from animal manure, and that vegetable crops in Japan received especially large amounts of P (122 kg P ha −1 year −1 ) through animal manure amendments. Livestock manure therefore contributed significantly to the observed soil P accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…In vegetables, the N balance decreased till the second survey, but showed a later increasing trend, attributable to increasing manure and chemical fertilizer N input. Mishima et al (2010b) calculated N balance on six crop groups in Japan without considering soil group, found a similar decreasing trend in N balance except in vegetables, and attributed the reduction mainly to reduced input of fertilizers. Among the Organisation for Economic Co-operation and Development (OECD) countries, an increased N balance was caused by intensification of livestock farming rather than by an increase in the application of chemical N fertilizers (OECD 2008).…”
Section: Dominant Soils In Crop Productionmentioning
confidence: 88%
“…Large N surpluses raise the risk of N leaching into groundwater (Nishio 2003;Mishima et al 2009). N has been especially over-applied to vegetables and tea (Camelia sinensis L.) (Mishima et al 2010b). In this paper, we assessed N and phosphate balance in six crop categories, although they cannot indicate the effect to farmland soils under different fertilization.…”
Section: Introductionmentioning
confidence: 99%